Studi Literatur: Kewirausahaan Sosial dan Tanggung Jawab Sosial Perusahaan - Wulanda, Fanny (Manajemen dan Kewirausahaan; Vol 13 No 1 (2022): Published in Jan 2022, 2022)
Social entrepreneurship belongs to the entrepreneurs who disclose non financial information along with financial information in a corporate social responsibility point of view. The link between enterprises and society, allows us to analyze that there are many things to be done to mitigate these effects of the current economic model in favor of improving the quality of life society. There are two alternate paths, that aim at the same ultimate goal, one is the Social Entrepreneurship which is intended to meet common needs resulting of the economic system and Corporate Social Responsibility, which it is the result of company ethical reflection based on interdependence and reciprocity of it to society, both paths are closely related to the creation of sustainable social value.